Hasil Produksi Ikan Patin (Pangasius sp.) pada Tiga Desa Berbeda di Kabupaten Ogan Ilir - Retno Cahya Mukti; Aulia Febi Anggraini; Adelta Marserona Nadeak; Adinda Gusti Maharani; Citra Kencana; Mesly Agnes Monica Simarsoit; M Satria Guntara (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2023)
Mukti RC, Anggraini AF, Maharani AG, Nadeak AM, Simarsoit MAM, Kencana C, Guntara MS. 2022. The production of catfish (Pangasius sp.) in theree different villages In Ogan Ilir District. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang 27 Oktober 2022. pp. 695-703. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Catfish (Pangasius sp.) is one of the most widely cultivated freshwater fish commodities. The current problem that occurs related to catfish yields lies in the location and application of different cultivation systems. This study aimed to determine the differences in the best farmed production results of catfish in three different villages. The method carried out is to conduct a interviews, field observations, and literature reviews. Interviews were conducted directly to fish farmers in Burai Village, Ulak Segelung Village, and Tanjung Pering as resource persons as well as conducting field observations with several literature studies on the source of information on the topic of discussion. The results showed that the location and application of different cultivation systems will affect the production of catfish. Cultivation location in Tanjung Pering Village with the use of water sources derived from rivers given alum and soda ash produce high production yields. While the best feeding frequency is applied in Burai Village by giving feed once a day at night using commercial pellets and additional feed in the form of fish - small fish is the best feeding method that produces high production results, followed up so that it can be applied to catfish farmers so that it can produce high production results. So it can be concluded that the best method of application. treatment and water is the villages of Tanjung Pering while the best method of applying feed is Burai Village. This activity needs to be followed up to get better implementation.